Constructing phase boundary in AgNbO3 antiferroelectrics: pathway simultaneously achieving high energy density and efficiency - Nengneng Luo (Nature Portfolio, 2020)
Dielectric capacitors are widely used in electronic systems but they possess inferior energy density in comparison with other electrochemical energy storage. Here, the authors construct a diffused phase boundary to simultaneously achieve high energy storage density and efficiency in AgNbO3antiferroelectrics.